Ti-C and CFs Work Together to Enhance the Comprehensive Tribological Properties of PTFE-Based Composites for the Manufacture of Wave Glider Power Shafts - Angang Yan; Xingju Yao; Yuan Wei; Qianjian Guo; Yulong Wang; Wuqiang Tang; Xian Xu (Lubricants, 2025)
Wave gliders’ power system shafts face complex conditions. To enhance their operational stability, it is crucial to study PTFE, a polymer material that could replace traditional metals. This study added carbon fiber (CF), titanium carbide (Ti-C), and both to a PTFE matrix. The impact of seawater immersion on water absorption and the mechanical properties was examined, as well as friction and wear characteristics under constant amplitude cyclic (CAC) loading and seawater lubrication. The results indicated that while Ti-C boosts PTFE matrix hardness, its poor binding with the PTFE matrix leads to high water absorption in Ti-C/PTFE (PTFE-3), causing a significant decrease in the mechanical properties post-immersion and poor friction and wear performance. In contrast, CFs and the PTFE matrix have good interfacial bonding and greatly improve the resistance of the PTFE matrix to cyclic loading and seawater immersion. Therefore, CF/PTFE (PTFE-2) shows good mechanical and tribological properties. Moreover, incorporating a certain amount of CFs into Ti-C enhances its adhesion to the PTFE matrix, reducing the occurrence three-body wear and allowing Ti-C to fully utilize its high hardness. Thus, the combination of Ti-C and CFs markedly improves PTFE’s mechanical and tribological properties under cyclic loading and in seawater.